Efficiency of arbitration computer with ratio of winning decisions in boxing - Sabri Abd El Hameed, A.; Hamed, N. I. (World Journal of Sport Sciences, 2010)
Boxing arbitration by Computer goes back to the year 1989. It was used at King Cup competition in Thailand 1989; the research tackles the problem of the new boxing arbitration by computer as it mainly depends on three Judges from five. The research aims to recognize winning ratio in contests for each weight category and winning ratio in contest for each boxing seasons (season 64, season32, season 16, quarter final, semi final, final).The researcher used the descriptive method with survey study. The sample of the research includes results for the world boxing championships for men in China 2005, which included 396 contests for 407 boxers. High Rate of contests finished in points by percentage 71,46%; Reduction of knock out head 0, 51% while came 17,6% in Olympic Gmes at Moscow 1980; boxers depend in getting points on technical excellence, reduction of finishing contests due to the outclass (RSCO) and disqualification (Disq) that reached to 0.76% for both of them to select the best boxers at this Olympics and rduction of head injury in 0,51% in good qualification at these championships. Interest, the concentration in pushing of the speedy fast hitting for justification of points since the first moment of contest, the speed and accuracy of beating by many points about winning, Training of boxers far from violence by positive speedy movement during practice of playing and concentration on individual, long hitting with double hitting in positive movement during attack and defense for justification of winning.